The impact of economic indicators, industrialization and pollutant emissions (CO2) on economic development in Malaysia / Saliza Sulaiman ... [et al.] - Sulaiman, Saliza; Ismail, Zuraidah; Sahudin, Zahariah; Azhar, Hazirah (Universiti Teknologi MARA Cawangan Selangor and UiTM Press, 2018)
The main purpose of this research is to identify whether there is any relationship between economic indicators, industrialization and pollutant emissions (CO2) on economic development in Malaysia. Economic indicators consist of government debt, health and education expenditure. This paper used Ordinary Least Square (OLS) Method to test the factors affecting the economic development. The data collection for each variable are collected from year 1980 until 2014 for 35 years in Malaysia. The result of the study shows that industrialization and pollutant emission (CO2) have a significant relationship on economic development. Meanwhile, government debt, health and education expenditure do not have a significant relationship on economic development. These finding will help to understand the effect of independent variables towards the dependent variable (economic development).